Main dimensions that impact knowledge management and university-business-government collaboration in the Brazilian scenario - Suzana Xavier Ribeiro; Marcelo Seido Nagano (REGE Revista de Gestão, 2018)
Purpose – The purpose of this paper is to investigate how certain characteristics of the university–industry–government collaboration facilitate knowledge creation and management, hence innovation focusing on particularities of the Brazilian scenario. Design/methodology/approach – As a conceptual basis, there are correlations between theories of knowledge management and the Triple Helix, a model referenced to university–industry–government cooperation. The research was conducted through a multiple case study at two National Institutes of Science and Technology (INCTs in Portuguese). Findings – The main results show the importance of participation in the INCT program, as it enables the creation of an organizational structure with the coordinator’s leadership, who directs the flow of knowledge among organizations and stimulates innovation. Originality/value – The choice of the topic is justified by the lack of studies on the identification and analyses of the main aspects of this type of collaboration in an integrated way.